AN ANALYSIS OF FEMINISM IN THE NOVEL THE GIRL WITH THE LOUDING VOICE BY ABI DARE - Gita Saputri; Harianto II Harianto II (Fakultas Sastra UMN AL Washliyah, 2023)
The study analyses the forms of feminism by Abi Dare. The Girl with the Louding Voice tells about the experience of girl who is tough, strong and brave. She experienced exploitation, oppression and slavery in a patriarchal society and was able to resist them. This research shows the forms of feminism movement by women. The purpose of this study is first, to find out the types of feminism contained in the novel. Second, to find out the resistance shown in the novel. This study uses a structuralism approach by Ferdinand de Saussure. The method used is a qualitative descriptive method to analyse the data source is taken from the story quote in the novel The Girl with the Louding Voice by Abi Dare. The findings in this study are first, the types of feminism that occur in The Girl With The Louding Voice novel are liberal feminism, Marxist feminism, socialist feminism and existential feminism. Second, the resistance shown the novel The Girl With TheLouding Voice is closed resistance and open resistance.